Using Soxhlet Ethanol Extraction to Produce and Test Plant Material (Essential Oils) for Their Antimicrobial Properties - James Redfern (American Society for Microbiology, 2014)
As the issue of antimicrobial resistance continues to grow, there is a renewed interest in deriving antimicrobial products from natural compounds, particularly extracts from plant materials. This paper describes how essential oil can be extracted from the common herb, thyme (Thymus vulgaris) in the classroom. Subsequently, the extract can be tested for its antimicrobial activity. A number of variables are suggested.